Development of a GIS Tool for Sustainable Urban Drainage Systems Evaluation. Issue 1 (May 2020) - Barreto, W; Ramos, N; Castro, K; Torres, J; Torres, R; Picón, R
Abstract: Climate change is forcing the development of new adaptation techniques. Drainage in the cities does not escape to this fact, requiring new techniques that allow the adaptation to the new changing scenarios. Usually, these new techniques for urban drainage systems are based in complex and detailed evaluation methods; therefore, they need to be easy to apply and have a strong physical basis for modelling the rainfall-runoff processes. This paper shows the integration of a geographic information system with a hydrodynamic model. The tool was developed in python language and is able to incorporate all the Low Impact Development techniques (LIDs) contained in the Storm Water Management Model. It was applied to an extreme rainfall event in the city of Cabudare in Venezuela. The drainage system of the city was tested with and without LIDs for comparison and validation of the tool. Results show that the tool is able to model the main drainage features in the city (streets, pipes and channels), showing a good performance. Also, it is a user-friendly tool for urban drainage evaluation.